Hybrid qualifications : structures and problems in the context of European VET policy - Deissinger, Thomas [Herausgeber]; Aff, Josef [Herausgeber]; Fuller, Alison [Herausgeber]; Jorgensen, Christian Helms [Herausgeber] (Lang, 2013)
"Against the background of increasing qualification needs there is a growing awareness of the challenge to widen participation in processes of skill formation and competence development. At the same time, the issue of permeability between vocational education and training (VET) and general education has turned out as a major focus of European education and training policies and certainly is a crucial principle underlying the European Qualifications Framework (EQF). In this context, "hybrid qualifications" (HQ) may be seen as an interesting approach to tackle these challenges as they serve "two masters", i.e. by producing skills for the labour market and enabling individuals to progress more or less directly to higher education. The specific focus of this book is placed on conditions, structures and processes which help to combine VET with qualifications leading into higher education. This volume assembles articles by researchers from Switzerland, the Netherlands, France, Australia, Canada, Scotland, England, Denmark, Austria and Germany." (Verlag; BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; I 2.3.5 Australien, Ozeanien; I 2.3.2 Nordamerika; I 2.1 Deutschland; EU-Bildungspolitik; Europäischer Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Doppelqualifikation; Schweiz; Niederlande; Frankreich; Schottland; Australien; Kanada; England; Dänemark; Österreich; Bundesrepublik Deutschland